MOBILE APPS DEVELOPMENT AND VALIDATION: TAILORED INTERVENTION ON DEPRESSION AMONG PARAMEDIC STUDENTS OF MALAYSIAN MINISTRY OF HEALTH TRAINING INSTITUTE AT KUCHING, SARAWAK - Abdullah, Nur Issyatul Sofea; Selamat, Neni Widiasmoro; Ismail, Nurul Azira; Irwanto (Malaysian Journal of Public Health Medicine, 2024)
Depression is rather common among students in any educational institution, with no exception for local students in Malaysia. Early depression intervention, such as boosting awareness of depression, has been documented in the literature as a helpful strategy to prevent this type of mental disease. Therefore, knowledge of depression was introduced through a mobile app to enhance the knowledge level of depression among paramedic students at Institut Latihan Kementerian Kesihatan Malaysia (ILKKM) Kuching, in Sarawak. An interventional study with convenience sampling was conducted among final-year paramedic students aged 22 to 27 years old. Knowledge of Depression for Students Questionnaire (KDSQ) and clinical vignette were used to assess the knowledge on depression before and after the intervention. The Knowledge of Depression for Student Mobile Application (KDS-App) consists of 12 sections and was used in intervention to enhance the knowledge of depression among the students. Assessment for knowledge of depression of the students via KDSQ reveals higher post-intervention knowledge score than the pre-intervention performance (P<0.05). The KDS-App as an intervention tool in this study contributes to greater improvement in students’ ability to recognize depression (93.0%), knowledge of appropriate first-aid for depression (98.3%), and ability to determine medical intervention for depression (99.1%). The control group presented no improvement in their knowledge of depression based on the clinical vignette and KDSQ assessments. Besides educating students about depression, this mobile app can also be used as a first-aid tool for depression; an alternative resource for anyone looking to learn more about depression, self-monitor for depression, or raise awareness of depression